Innovation in the language of the Vietnamese short story apter 1975 - Que, Nguyen Thi Thanh (VNU Journal of Science: Social Sciences and Humanities, 1999)
In this article, an a tte m p t is made to explore an interesting by neglected language phenomenon in discourse, which has been referred to by systemicists such as Halliday (1994), Halliday & Martin (1993), and Matthiessen (1992, 1995) as grammatical metaphor. What is grammatical metaphor? And how can grammatical metaphors be classified in Vietnamese. The article begins by exploring the notion of realisation in the systemic functional model as it is the key to understanding grammatical metaphor. Then an attem p t is made to classify grammatical metaphors into four categories: logical experiential, interpersonal^ and textual. The article concludes th a t grammatical metaphor is a an infinite resource and crucial method in developing (particularly scientific) discourse. It is therefore recommended that linguists, particularly discourse analystâ should carry out further research into this area knowledge.'